Analisis Kinerja dan Fasilitas Aksesibilitas Unit Pelayanan Khusus Bagi Penyandang Disabilitas Di Bandar Udara Internasional i Gusti Ngurah Rai Bali - Michelle; Yunus Purnama (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Airports are required to provide flight comfort and safety with reliable facilities and services, especially for persons with disabilities by providing services that are easy to understand, easy to follow and easy to implement. One of the airports that very well manages its services and facilities, namely I Gusti Ngurah Rai Airport in Bali, this is one of PT Angkasa Pura I's efforts to gain the trust of passengers, especially passengers with disabilities who use air transportation services at I Gusti Ngurah Rai Airport in Bali. . This study aims to determine the performance of the special service unit when serving passengers and how accessible the facilities are for passengers with disabilities. The research was conducted in the international and domestic terminal areas of I Gusti Ngurah Rai Airport in Bali using qualitative research methods. Sources of data in this study using primary and secondary data. Data collection techniques in this study used observation, interviews and documentation. The data analysis technique in this study is the data reduction stage, the data presentation is then followed by the final step, namely drawing conclusions. The results of this study conclude that efforts to improve service provide satisfactory results, this is based on observation and interview activities that have been conducted by researchers during research at I Gusti Ngurah Rai Airport in Bali where special service unit officers serving passengers with disabilities are in accordance with operational standards procedures (SOPs). It's just that the quantity of three officers in one shift is still not enough considering that I Gusti Ngurah Rai Airport service users in Bali are increasing every year and special facilities for passengers with disabilities in all areas of I Gusti Ngurah Rai Airport in Bali are sufficient. This is based on observations made by researchers regarding the disability facilities provided..